The Effects of Core Stability Exercise in Improving Back Muscle Strength, Limb Muscles and Dynamic Balance in the Elderly in Singaraja, Indonesia - Bagiartana, Kadek Dio Agus; Huriah, Titih (Fakultas Ilmu-ilmu Kesehatan, 2023)
Balance disorders are a severe problem for the elderly. Exercise that can increase the power of the back muscles, leg muscles and dynamic balance is physical exercise in core stability exercise (CSE). This study aimed to analyse core stability exercise's effect on increasing back muscle strength, leg muscles, and dynamic balance in the elderly. Fifty-six elderly people aged 60-70 years were selected by simple random sampling as the sample in this study. The exercise program was given CSE (n: 28) for four weeks as the intervention group. The back and leg muscle strength were measured using the Back-leg dynamometer and balance measurement using the Time Up Go Test (TUGT). T-test and Mann-Whitney analyses were used to compare the results before and after the intervention. The different tests between the intervention and the control group obtained a p-value of 0.001, meaning an effect of CSE to increase the strength of the back muscles, leg muscles, and dynamic balance in the elderly existed. This study proved that CSE effectively increased back muscle strength, leg muscles and dynamic balance in the elderly. It is suggested to analyze the effectiveness of CSE based on the characteristics of the respondents.